A history of collective resilience and collective victimhood: Two sides of the same coin that explain Black Americans' present‐day responses to oppression. (29th July 2022) - Selvanathan, Hema Preya; Jetten, Jolanda; Umeh, Alexis
Abstract: Collective victimhood and collective resilience are two sides of the same coin. However, most literature to date has focused on the experiences and consequences of collective victimhood. In the present research, we focused on the experiences of Black Americans, a group that has a legacy of victimization and resilience. As a part of Black Americans' collective memory, we explored the nature of historical collective resilience and examined its role in explaining collective responses to present‐day oppression, over and above any effect of historical collective victimhood. When they were asked to reflect on their group's history, across Studies 1 ( N = 272) and 2 ( N = 294), we found that Black Americans generated narratives of collective resilience. In both studies, we also found evidence that perceived historical collective resilience was linked to a greater sense of collective continuity, which, in turn, explained greater support for the ongoing Black Lives Matter movement. Our findings underscore the importance of considering narratives of resilience in a group's history and point to the way such collective resilience narratives can serve as a resource for the group in the present.